Participating in Longitudinal Observational Research on Psychiatric Rehabilitation: Quantitative Results From a Patient Perspective Study - Dehn, Lorenz B.; Driessen, Martin; Steinhart, Ingmar; Beblo, Thomas (Frontiers in Psychiatry, 2022)
Background Longitudinal observational studies play on an important role for evidence-based research on health services and psychiatric rehabilitation. However, information is missing about the reasons, why patients participate in such studies, and how they evaluate their participation experience. Methods Subsequently to their final assessment in a 2-year follow-up study on supported housing for persons with severe mental illness, n = 182 patients answered a short questionnaire on their study participation experience (prior experiences, participation reasons, burden due to study assessments, intention to participate in studies again). Basic respondent characteristics as well as symptom severity (SCL-K9) were also included in the descriptive and analytical statistics. Results To help other people and curiosity were cited as the main initial reasons for study participation (>85%). Further motives were significantly associated with demographic and/or clinical variables. For instance, “relieve from boredom” was more frequently reported by men and patients with substance use disorders (compared to mood disorders), and participants ‘motive” to talk about illness” was associated with higher symptom severity at study entry. Furthermore, only a small proportion of respondents indicated significant burdens by study participation and about 87% would also participate in future studies. Conclusions The respondents gave an overall positive evaluation regarding their participation experience in an observational study on psychiatric rehabilitation. The results additionally suggest that health and social care professionals should be responsive to the expectations and needs of patients with mental illness regarding participation in research.